The implementation of blended learning models based liveboard against affective aspects in modern physics course - Feli Cianda Adrin Burhendi; Afif Abdurrozak; Soenarto Soenarto (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to know the implementation of blended learning models using liveboard to affective aspects in modern physics course. The method used in this study was a pre-experimental design (nondesign) with the design of the study one group pretest-posttest design. The population in the study were all students of physics education UHAMKA. The sample used purposive sampling entire fourth-semester students of physics education as many as 22 people. To view the affective aspects of the modern physics course as evidenced by calculating the index gain. The results of N-gain in the course of modern physics based on a questionnaire obtained a practical value of 0.59 with a percentage of 62.82 percent of student's possible value. Results of simple linear regression demonstrate the importance of Y = 45.578 + 0,422X. Based on the cost can be seen that the learning model of blended learning influences the affective aspects of students. In the hypothesis test, used t-test obtained in modern physics tcount = 1,818 with ttable = 1.717 at α = 0.05, so H0 was rejected, which states that there was a significant influence on learning using blended models based learning liveaboard terms of affective aspects.